Attraction agglomeration and destination appeal. (December 2016) - Bo, Zhou; Hailin, Qu; Ningqiao, Li
Using panel data from 225 cities in China over the 2002–2012 period along with dynamic panel data models, this study aims to quantify the impact of attraction agglomeration (AA) on the appeal of a destination at the macrolevel. The study results show that the agglomeration of natural and cultural attractions contributes to destination appeal in domestic tourism markets. The agglomeration of natural, cultural, and man-made attractions enhances destination appeal in international tourism markets. The agglomeration of cultural attractions has the most significant contribution in both domestic and international tourism markets. This study also demonstrates the lock-in effect of AA of a certain type, which means that diversification of attraction type will undermine the benefits of AA of a specific type. The results should help governments and industry organizations plan and develop regional tourism more effectively.